2012
DOI: 10.3758/s13423-012-0331-x
|View full text |Cite
|
Sign up to set email alerts
|

Novice motor performance: Better not to verbalize

Abstract: Offline verbalization about a new motor experience is often assumed to positively influence subsequent performance. Here, we evaluated this presumed positive influence and whether it originates from declarative or from procedural knowledge using the explicit/implicit motorlearning paradigm. To this end, 80 nongolfers learned to perform a golf-putting task with high error rates (i.e., explicit motor learning), and thus relied on declarative knowledge, or low error rates (i.e., implicit motor learning), and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Taken together, this research suggests that as the complexity of the cultural learning task increases, the more Type I processes will be implicated (Lee 1995). In fact, if learners of a complex motor skill attempt to consciously focus on their movements, or even verbalize rules for task completion, this can hinder acquisition of the skill (Chauvel et al 2013; Wacquant 2004; Wulf, McNevin, and Shea 2001). As a result, the (natural, built, and social) environment automatically engenders Type I cultural acquisition, which is largely outside conscious reflection (Bourdieu 1990).…”
Section: Learning Remembering Thinking and Actingmentioning
confidence: 99%
“…Taken together, this research suggests that as the complexity of the cultural learning task increases, the more Type I processes will be implicated (Lee 1995). In fact, if learners of a complex motor skill attempt to consciously focus on their movements, or even verbalize rules for task completion, this can hinder acquisition of the skill (Chauvel et al 2013; Wacquant 2004; Wulf, McNevin, and Shea 2001). As a result, the (natural, built, and social) environment automatically engenders Type I cultural acquisition, which is largely outside conscious reflection (Bourdieu 1990).…”
Section: Learning Remembering Thinking and Actingmentioning
confidence: 99%
“…An example of an analogy used to teach a basketball shooting task is "Shoot the ball as if you are trying to put cookies into a cookie jar on a high shelf" . Both, errorless learning and analogy learning, have been shown to lead to similar, or even better, motor skill performance compared to explicit learning (Maxwell et al, 2001, p. 14,15,16,17;Chauvel et al, 2013;Lam et al, 2010;Savelsbergh et al, 2012). Nevertheless, evidence about the learning process that takes place is mixed (Kal et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In these domains, it may be better not to put what one is learning into words at certain intermediate skill levels. In contrast, recent findings in the motor domain showed that verbalizing a previous motor experience (golf putting) can have detrimental effects upon subsequent skilled performance [5] and, most surprisingly, upon novice performance in particular when learning conditions promoted the use of nonverbal procedural knowledge [4]; for a method manipulating the type of knowledge developed at the outset of learning, see, [30], [31]; for a review, see [32]. Future research should help gaining insight into when, for which type of task and for whom recourse to words enhances or, on the contrary, hinders learning and performance.…”
Section: Discussionmentioning
confidence: 86%
“…This kind of learning is not only perceptual but also conceptual: learners observe and memorize a sequence of movements occurring in succession and, because each single movement composing the sequence is unique, they need to break down the sequence into its single units in order to analyze every unit in depth. The present study attempts to determine the extent to which visual memory for previously-seen sequence of fencing movements is affected by verbalization (for the influence of verbalization on motor tasks, see, [4], [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%